2010
DOI: 10.1186/1471-2474-11-236
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain: what determines functional outcome at six months? An observational study

Abstract: BackgroundThe rise in disability due to back pain has been exponential with escalating medical and societal costs. The relative contribution of individual prognostic indicators to the pattern of recovery remains unclear. The objective of this study was to determine the prognostic value of demographic, psychosocial, employment and clinical factors on outcome in patients with low back painMethodsA prospective cohort study with six-month follow-up was undertaken at a multidisciplinary back pain clinic in central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…A connected predictor was found to be of relevance by another group of researchers, who adopted a follow-up similar to ours. Harms et al found an episodic pain character to be advantageous [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A connected predictor was found to be of relevance by another group of researchers, who adopted a follow-up similar to ours. Harms et al found an episodic pain character to be advantageous [19].…”
Section: Discussionmentioning
confidence: 99%
“…An additional value of these large trials (n≥500) is the setting, since patient samples were from primary health care, which occurs rather seldom. Harms et al accomplished a cohort study at a multidisciplinary back pain clinic, in which among others physiotherapists were practicing [19].…”
Section: Introductionmentioning
confidence: 99%
“…Negative beliefs about LBP was only reported in one other study as an independent risk factor for poor recovery [31], and was associated with high back pain intensity levels in a cross-sectional study [32]. Continuous back pain was reported as a factor for poor recovery in only one study [33]. The question about the presence of continuous back pain independent of posture or activity is often used in primary care, but is not often examined in prognostic studies.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…More than 12 weeks In addition, on the guideline search we found 15 studies in our systematic search on PubMed and included 10 systematic reviews for selecting individual prognostic factors [57][58][59][60][61][62][63][64][65][66][67]. We found that catastrophizing and somatization seem to be negatively associated with recovery of NSLBP [58,59].…”
Section: Processmentioning
confidence: 99%